Integrating ViralFlow and MacWorP for Automated Viral Genomic Surveillance Workflows - Pinho, Raphael; Almeida, Sintia; Simões, Roberto; Kahwage, Cassia; Amaris, Marcos (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2026)
We present an integrated web platform combining ViralFlow and MacWorP for automated viral genomic surveillance through distributed workflow orchestration and accessible web-based execution. A proof-of-concept deployment demonstrated the feasibility of integrating specialized viral genomics pipelines within a scalable workflow management environment. Preliminary results indicate gains in accessibility, reproducibility and distributed processing, supporting the potential of the platform as a modular framework for genomic surveillance in public health laboratories.